Foundations of Information Science. Issue 1 (13th October 2021) - Bates, Marcia J.; Buckland, Michael K.; de Fremery, Wayne; Wang, Lin
Abstract: The foundations of information science define our field and, thereby, our professional identity. It follows that if our our professional identity is to be equitable, diverse, inclusive, and relevant, then the foundations of our field should also be. Three diverse contributions to the foundations of information science will illustrate diverse approaches to making information science more complete will be illustrated by experienced panelists with different backgrounds: Recuperating neglected work; exploring alternative methods; and drawing attention to undocumented work. Marcia Bates will revisit early work on information seeking. Michael Buckland and Wayne de Fremery will demonstrate an alternative approach to the problematic concept of "context." Lin Wang will introduce aspects of the early history of information science in China.